Abstracts of the International Science of Aphasia Conference, University of Bordeaux, September 2022 - Redactie SSTP (University of Groningen Press, 2022)
Abstracts and programme of the International Science of Aphasia Conference, University of Bordeaux, September 12-15, 2022